أثر سياسة توزيع الأرباح على القيمة السوقية للسهم دراسة ميدانية - مرعي, عبد الرحمن; زكريا, نائلة (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تهدف الدراسة إلى تبيان مدى العلاقة بين سياسة الإدارة في توزيعات الأرباح كمتغيرات مستقلة والقيمة السوقية للسهم كمتغير تابع. ولتحقيق هذا الهدف قام الباحث بإجراء مسح للدراسات المحاسبية والمالية المتعلقة بهذا الموضوع ومن ثم قام بإجراء دراسة ميدانية من خلال إعداد استبيان وزع على عدد من المستثمرين والعاملين في شركات الوساطة المالية في سوق دمشق للأوراق المالية و عدد من الأكاديميين في كلية الاقتصاد ، تم تحليل الاستبيان من خلال استخدام برنامج SPSS وأظهرت النتائج وجود علاقة بين توزيعات الأرباح وبالأخص التوزيعات النقدية المنتظمة والقيمة السوقية للسهم، وكذلك وجود علاقة بين تغير سياسة التوزيعات والقرار الاستثماري. This study aimed to identify the impact of dividends policy as an independent variable on the stock market value as dependent variable. The researcher relies on relevant accounting and financial studies. Then the researcher conducted a field study through the preparation of a questionnaire distributed to a number of investors and workers in brokerage firms at Damascus Stock Exchange and academics at Damascus University. The researcher used SPSS program to analyze the questionnaire. The researcher finds a significant correlation which exists between the type of dividends (especially regular cash dividends payment) and investor’s desire to buy the stock and finally the market value. Besides that, there is a relationship between changes in the dividends policy and its effect on the stock price.